sin 6 x + cos 6 x = 4 1
Solve for x in degrees, for 0 ∘ < x < 9 0 ∘ :
Source: VMO 1962
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
(sinx)^6+(cox)^6=[(sinx) ^2+(cox)^2]^3 - 3(sinx)^2(cosx)^2[(sinx)^2+(cosx)^2]=1-3(sinx)^2(cosx)^2. Therefore 1-3(sinx)^2(cosx)^2=(1/4). Or 4(sinx)^2(cosx)^2=1 or sin(2x)=1 (since x<90 degrees, therefore sin(2x)>0) or 2x=90 degrees or x=45 degrees .
With the following two conditions known, it's easy to solve this problem:
Assume s i n 2 x = a , and
s i n 2 x + c o s 2 x = 1
Substituting (1) into the equation gives a 3 + ( 1 − a ) 3 = 4 1
By expansion, a 3 + ( 1 − 3 a + 3 a 2 − a 3 ) = 4 1
3 a 2 − 3 a + 4 3 = 0
a 2 − a + 4 1 = 0
( a − 2 1 ) 2 = 0
a = 2 1
Since s i n 2 x = 2 1 , s i n x = 2 2
x = 4 5 ∘
Here is a lazy solution: the question only states 1 x value with the interval that makes the equation true. The sin and cos graphs for the given interval are positive and symmetrical about x = 45°,the same goes for their 6 powers. Now if there is a solution other than 45°, there will be 2 solutions one x, and the other 90° - x. But since the question only asks for one solution, x must then be 45°. Substituting this in show sthat it is a solution
Problem Loading...
Note Loading...
Set Loading...
( sin 2 x + cos 2 x ) 3 1 1 = sin 6 x + 3 sin 4 x cos 2 x + 3 sin 2 x cos 4 x + cos 6 x = sin 6 x + cos 6 x + 3 sin 2 x cos 2 x ( sin 2 x + cos 2 x ) = sin 6 x + cos 6 x + 4 3 sin 2 2 x
⟹ sin 6 x + cos 6 x 1 − 4 3 sin 2 2 x sin 2 2 x sin 2 x 2 x ⟹ x = 1 − 4 3 sin 2 2 x = 4 1 = 1 = 1 = 9 0 ∘ = 4 5 ∘ for 0 ∘ < x < 9 0 ∘